The year in television, 2009 a catalog of new and continuing series, miniseries, specials and tv movies - Terrace, Vincent, 1948- (Year in television, 2010)
"Included are series, TV movies, aired pilots, specials, miniseries and Internet series. Alphabetically arranged entries provide casts, storylines, production credits, networks, broadcast dates, and excerpts from newspaper reviews. New to this volume is a listing of the highlights of the year and coverage of all the unaired pilots produced for the 2008-2009 season"--Provided by publisher.